Transversus Abdominis Plane Block Versus Caudal Epidural for Lower Abdominal Surgery in Children: A Double-Blinded Randomized Controlled Trial. (August 2015) - Bryskin, Robert B.; Londergan, Bevan; Wheatley, Rebekah; Heng, Renee; Lewis, Marjorie; Barraza, Mark; Mercer, Erica; Ye, Gang
Abstract : BACKGROUND: Transversus abdominis plane block (TAPB) has emerged as a safe and effective regional anesthesia technique for providing postoperative lower abdominal analgesia. Complications associated with TAPB are rare and pose a lower overall risk to the patient receiving a TAPB versus a caudal block, which is considered the gold standard for pediatric lower abdominal regional anesthesia. Our study hypothesis was that TAPB would initially be equivalent to caudal block in providing postoperative pain control but would also show improved pain relief beyond the anticipated caudal duration. METHODS: This study was a double-blinded randomized controlled trial. Forty-five children between the ages of 1 and 9 undergoing bilateral ureteral reimplantation surgery through a low transverse incision were enrolled. Narcotic requirement, pain scores (FLACC/Wong-Baker FACES), episodes of emesis, and antispasmodic requirement were recorded in the postanesthesia care unit (PACU) and at 6-hour intervals for 24 hours from the time of block placement. Our protocol used a multimodal approach toward pain management in all children, including randomized regional technique, scheduled ketorolac, morphine as needed, and the antispasmodic, oxybutynin, as needed. RESULTS: Morphine requirement showed no statistical difference during the initial 12 hours (all P ≥ 0.68 at PACU, 6 and 12 hours). However, at 24 hours those patients randomized to receive the TAPB required less cumulative morphine than the caudal group (0.05 mg/kg ± 0.06 vs 0.09 mg/kg ± 0.07, P = 0.03). There was a trend toward fewer episodes of emesis in the TAPB group which reached statistical significance at 18 and 24 hours (6 vs 1 episodes, P = 0.03; and 9 vs 2 episodes, P = 0.02). Pain scores (0–10) were higher in the TAPB group in the PACU (3.46 ± 2.69 vs 1.71 ± 2.1, P = 0.02), but there were no significant differences at all subsequent time points (all P ≥ 0.10). The TAPB group also had a higher requirement for the bladder antispasmodic oxybutynin at 24 hours (0.49 ± 0.58 vs 0.28 ± 0.17, P = 0.003). CONCLUSIONS: TAPB provided superior analgesia compared with the caudal block at 6 to 24 hours after block placement, as demonstrated by a statistically significant decrease in cumulative opioid requirement, which was the primary end point. The lower incidence of emesis in the TAPB group likely reflected the decreased opioid consumption. Although TAPB appears to be less effective than the caudal block in preventing viscerally mediated bladder spasms, as evidenced by the higher PACU pain scores and increased oxybutynin requirement at 24 hours, this effect may be counteracted in future clinical practice by scheduled administration of the antispasmodic medications. Considering the overall safety advantages of the TAPB over the caudal block, this should be considered a preferred regional technique for lower abdominal surgeries. Abstract : Published ahead of print April 21, 2015